40 Years of Experience with the National Market System (NMS) Who Are the Winners and What Have We Learned? - Schwartz, Robert A.; Byrne, John Aidan; Stempel, Eileen (Cham : Springer International Publishing : Imprint: Springer, 2022)
In 1975, the U.S. Securities Acts Amendments were enacted by Congress, which amongst other measures, officially mandated development of a National Market System (NMS). Since that time, the competitive map has been redrawn, technological changes have been huge and pervasive in scope, and the landscape is ever-changing. This book looks at the evolution of NMS and the factors that have influenced it since its development. Titled after the Baruch College Financial Markets Conference, 40 Years of Experience with the National Market System (NMS): Who Are the Winners and What Have We Learned, the book examines the following questions: What is liquidity and how is it best measured and provided? Has NMS-Induced competition delivered? What is technology's challenge to regulators? Are fair and level playing fields a good regulatory goal? What is the buyside's view? The Zicklin School of Business Financial Markets Series presents the insights emerging from a sequence of conferences hosted by the Zicklin School at Baruch College for industry professionals, regulators, and scholars. The transcripts from the conferences are edited for clarity, perspective and context; material and comments from subsequent interviews with the panelists and speakers are integrated for a complete thematic presentation. Each book is focused on a well delineated topic, but all deliver broader insights into the quality and efficiency of the U.S. equity markets and the dynamic forces changing them.
Chapter 1. Thoughts and Perspectives on 40th Anniversary of the National Market System (NMS) -- Chapter 2. Technology's Challenge to Regulators -- Chapter 3. The Global View -- Chapter 4. Has NMS-Induced Competition Delivered? -- Chapter 5. Fair and Level Playing Fields: A Good Regulatory Goal? -- Chapter 6. What Have We Learned? -- Chapter 7. The Buyside Responds -- Chapter 8. Invited Editorial: Combating Turbulence in the Equity Markets: Get the Listed Companies on Board.
Keywords: Financial services industry; Business enterprises-Finance.; Risk management; Financial Services; Corporate Finance; IT Risk Management